Investigating the Efficacy of Saccharomyces boulardii in Metabolic Syndrome Treatment: A Narrative Review of What Is Known So Far - Egea, Mariana Buranelo; Oliveira Filho, Josemar Gonçalves de [UNESP]; Lemes, Ailton Cesar (MDPI, 2023)
Metabolic syndrome (MetS) is characterized by complex metabolic changes involving a cluster of co-occurring conditions, such as abdominal obesity, high blood pressure, high fasting plasma glucose, high serum triglycerides, and high LDL cholesterol levels or low HDL cholesterol levels. The incidence and risk factors of MetS occurrence increase every year. It is estimated that MetS affects approximately 30% of the population of some countries. Therefore, novel strategies are being studied to reduce the negative impact of having an unbalanced diet and a lack of physical activity. One of these strategies is the administration of probiotic microorganisms, such as the yeast Saccharomyces boulardii, which has been associated with several beneficial health effects (including modulation of the intestinal microbiota and improvement of the inflammatory, antioxidant, antibacterial, antitumor, and anti-inflammatory profiles). Thus, the objective of this study was to review the risk factors of MetS occurrence and the beneficial effects of S. boulardii ingestion in the treatment of MetS. Here, we critically evaluate the treatment necessary to promote these benefits. Using the pre-established inclusion criteria, eight studies were reviewed, including five animal and three human studies. The results reported the regulation of the lipid profile, modulation of the intestinal microbiota and gene expression, and a decrease in mass gain as positive results when S. boulardii was administered. Although more experiments are needed to validate these results, especially using human models, there is a trend toward improvement in MetS and a reduction in its risk factors with the administration of S. boulardii.
Keywords: health benefits; healthy diet; intestinal modulation; probiotics; yeast